Effect of Routine Active Management of Third Stage of Labor on Postpartum Hemorrhage at Wang Nuea Community Hospital - Pathumbal, Arakka (Journal of Health Science of Thailand, 2019)
The objective of this retrospective cohort study was to compare the effect of active versus expectant management of third stage of labor on blood loss, postpartum hemorrhage and maternal complications in rural setting at Wang Nuea Hospital, Lampang. Retrospective data of women having single on vaginal births in September 2005- July 2007 at Wungnua Hospital was collected. Estimated blood losses were compared between women received active management in the third stage of labor (154 cases) versus expectant management (229 cases). The other outcomes included duration of third stage of labor, maternal complications and fetal outcomes. The routine active management of third stage of labor resulted in less postpartum maternal blood loss was observed. Moreover, shorter third stage of labor time, frequency of retain placenta and significantly less frequent hypovolemic shock were reported in the active management group. This study shows a trend that routine active management of third stage of labor in Wungnua Community Hospital is as effective in reducing maternal blood loss as reported in other randomized trials in large institutions. The practice is also feasible and useful in preventing postpartum hemorrhage in community hospital.